Peran Moderasi Ukuran Perusahaan Pada Biaya Audit Terhadap Kualitas Audit Pada Perusahaan Sub Sektor Barang Konsumsi di BEI - Azolla Degita Azis; Desmy Riani; Lutphy Raihana Suci (CV. ITTC INDONESIA, 2025)
This research aims to test whether the size of the company can strengthen the influence of audit costs on audit quality. The data used is secondary data sourced from the Indonesia Stock Exchange website. The sampling technique uses purposive sampling. The population in this study consists of manufacturing companies in the consumer goods sub-sector from 2018 to 2022, totaling 58 companies with a period of observation over 5 years. Based on the established criteria, 20 companies were selected as research samples, resulting in a total sample size of 100. This research is a quantitative study using the Logistic Regression method. The research results show that the size of the company does not strengthen the influence of audit fees on audit quality. These research findings can serve as additional literature in the field of accounting and financial auditing. For future research, it is recommended to conduct studies with a larger sample size and different subjects, so as to produce varied research conclusions that can be considered by regulators.